2020
DOI: 10.1016/j.neuron.2020.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Deep Reinforcement Learning and Its Neuroscientific Implications

Abstract: The emergence of powerful artificial intelligence is defining new research directions in neuroscience. To date, this research has focused largely on deep neural networks trained using supervised learning, in tasks such as image classification. However, there is another area of recent AI work which has so far received less attention from neuroscientists, but which may have profound neuroscientific implications: deep reinforcement learning. Deep RL offers a comprehensive framework for studying the interplay amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
130
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(133 citation statements)
references
References 146 publications
(194 reference statements)
3
130
0
Order By: Relevance
“…Learning and building artificial intelligence (AI) agents capable of interacting with their environment are major objectives in the fields of ML and AI. Deep artificial neural networks (73) have demonstrated great success over the recent years, particularly in the domains of image recognition, natural language processing, and deep reinforcement learning (74,75). Three challenges currently hamper further progress in the theoretical understanding of deep neural networks.…”
Section: Odor-background Segregation: a Joint Effect Of Temporal And mentioning
confidence: 99%
“…Learning and building artificial intelligence (AI) agents capable of interacting with their environment are major objectives in the fields of ML and AI. Deep artificial neural networks (73) have demonstrated great success over the recent years, particularly in the domains of image recognition, natural language processing, and deep reinforcement learning (74,75). Three challenges currently hamper further progress in the theoretical understanding of deep neural networks.…”
Section: Odor-background Segregation: a Joint Effect Of Temporal And mentioning
confidence: 99%
“…By mapping between language and the corresponding neural activity, recent studies have harnessed machine learning to decode linguistic information from the brain [24][25][26][27][28][29][30][31][32] . Taking a step forward, some theoretical and empirical work, especially in visual neuroscience 18,[33][34][35] , but recently also in language [25][26][27][28][29][30][31]36 , posits that deep neural networks may provide a new modeling framework to study neural computations in biological neural networks. To substantiate the call for this paradigm shift, we provide new behavioral and neural evidence for the connection between prediction-based DLMs and the human brain as they process natural speech.…”
Section: Introductionmentioning
confidence: 99%
“…When learning was not complete after the first success trial, furthermore, the data showed substantial though not complete preservation of the frontal explore state.While reward prediction error is an integral part of many learning processes, additional processes may be critical in rapid, model-based role learning. Our results are reminiscent of recent work on deep reinforcement learning, where meta-learning can allow rapid hypothesis-driven experimentation to replace slow parameter tuning(33).Evidently, a learned task model must govern the shift in frontal state that accompanies and may implement the switch from explore to exploit. An important open question is how this model is created.…”
mentioning
confidence: 64%